Circulating the peripheries: Small publishers, short story collections and Madinah: City Stories from the Middle East. - Miller, Ana K. (Journal of Commonwealth Literature, 2015)
Given widespread criticism of the hierarchies of the world literary system that privilege certain languages, regions, styles, and genres, this article explores the value of small publishers and short story collections that resist trends within commercial publishing. Taking Comma Press as a case study, the article investigates how the paratext and collected stories of Madinah: City Stories from the Middle East operate against the marginalization of the region’s literatures in commercial Anglophone publishing. Although such publications remain within a system that produces and packages the margins for consumption in the centre, by circulating less well-known writers and regions they can play a valuable role in expanding canons of world literature.